CHOICE OF PARAMETERS FOR COMBINED RENEWABLE ENERGY INSTALLATIONS - Olimov O.N., Narimanov B.A., Suyarov A.O., Sorimsokov U.S. (Academia Science Repository, 2023)
The calculation of the economic characteristics of RES installations with known TE characteristics can be carried out in the usual ways. However, the variability of RES and, in connection with this, the variability of energy characteristics requires that these features of RES be taken into account in the calculations